مستوى الاحتراق النفسي لدى عمال الصحة العمومية بولاية الأغواط في ظل جائحة كورونا - بوجرانة زهرة; سعدي عائشة; تجاني جرادي (My University, 2021)
The current study aimed to reveal the level of psychological burnout among public health users in the state of Laghouat in light of the Covid-19 pandemic, in addition to knowing the significance of the differences in both psychological burnout, gender variables and years of experience among the study sample. It consists of (35) health workers from the study population of (50), specifically from the public hospital Ahmed bin Ajila of the state of Laghouat. They were selected intentionally, and the "Maslash" scale was used to measure psychological burnout. A group of statistical methods were also relied on. In data processing, the results of the study showed: A high level of psychological burnout among health workers in light of the Corona pandemic.. There are statistically significant differences in occupational stress among health sector workers during the Corona (COVID-19) crisis due to the gender variable.burnout, covid-19, health workers